IFRD1 is required for maintenance of bladder epithelial homeostasis - Bisiayo E. Fashemi; Amala K. Rougeau; Arnold M. Salazar; Steven J. Bark; Rayvanth Chappidi; Jeffrey W. Brown; Charles J. Cho; Jason C. Mills; Indira U. Mysorekar (iScience)
Summary: The maintenance of homeostasis and rapid regeneration of the urothelium following stress are critical for bladder function. Here, we identify a key role for IFRD1 in maintaining urothelial homeostasis in a mouse model. We demonstrate that the murine bladder expresses IFRD1 at homeostasis, particularly in the urothelium, and its loss alters the global transcriptome with significant accumulation of endolysosomes and dysregulated uroplakin expression pattern. We show that IFRD1 interacts with mRNA-translation-regulating factors in human urothelial cells. Loss of Ifrd1 leads to disrupted proteostasis, enhanced endoplasmic reticulum (ER stress) with activation of the PERK arm of the unfolded protein response pathway, and increased oxidative stress. Ifrd1-deficient bladders exhibit urothelial cell apoptosis/exfoliation, enhanced basal cell proliferation, reduced differentiation into superficial cells, increased urothelial permeability, and aberrant voiding behavior. These findings highlight a crucial role for IFRD1 in urothelial homeostasis, suggesting its potential as a therapeutic target for bladder dysfunction.